Analyzing Anisotropy in 2D Rhenium Disulfide Using Dichromatic Polarized Reflectance. Issue 17 (21st March 2022) - Wen, Ting; Li, Jing; Deng, Qingyang; Jiao, Chenyin; Zhang, Maodi; Wu, Song; Lin, Lin; Huang, Wen; Xia, Juan; Wang, Zenghui
Abstract: In‐plane anisotropy in 2D rhenium disulfide (ReS2 ) offers intriguing opportunities for designing future electronic and optical devices, and toward such applications, it is crucial to identify the crystal orientation in such 2D anisotropic materials. Existing spectroscopy or electron microscopy methods for determining the crystalline orientation often require complicated sample preparing procedures and specialized equipment, which could sometimes limit their application. In this work, a dichromatic polarized reflectance method is demonstrated, which can quickly and accurately resolve the crystal orientation (Re–Re chain) in 2D ReS2 crystals with different thicknesses. Furthermore, it can be readily extended to multi‐chromatic schemes to achieve greater measurement capability and can be easily tailored to work for different 2D materials. The method offers a simple and effective approach for studying anisotropy in 2D materials. Abstract : A dichromatic polarized reflectance method is demonstrated, which can quickly and accurately resolve the crystal orientation (Re–Re chain) in 2D ReS2 crystals with different thicknesses. It can further be extended to multi‐chromatic schemes to achieve greater measurement capability, and be easily tailored to work for different 2D materials, thus offering a simple and effective approach for studying 2D anisotropy.